(untitled) (Journal of actual problems of jurisprudence, 2018)
Mediation – a process of negotiation in which the mediator, the mediator organizes and manages the negotiations so that the parties have come to the most favorable realistic and satisfying the interests of both parties to the agreement, as a result of which the parties settle the conflict between them. In the decision to terminate the mediation of the dispute on certain conditions accepted by the parties, as the mediator does not have the authority to make any binding decision on the parties to the dispute. The role of the mediator is to help the parties understand each other better, to reach an agreement; in some cases – help to find the options for the terms on which the dispute can be settled. Key words: mediation, representative.